A simplified clinical frailty scale predicts mortality in emergency department patients with acute dyspnea - Zwawi, Ahmad; Wessman, Torgny; Wändell, Per; Melander, Olle ; 0000-0002-2581-484X; Carlsson, Axel C.; Ruge, Toralph (GeroScience, 2025)
To evaluate a simplified version of the Clinical Frailty Scale (SCFS) among older adults presenting to the emergency department (ED) with acute dyspnea. In this retrospective single-center cohort study, we included patients from the Acute Dyspnea Study (ADYS) cohort. Severity of illness was assessed using the Medical Emergency Triage and Treatment System (METTS). SCFS was operationalized using existing data on municipal care services from the ADYS database and divided into three levels. SCFS 1: Not frail patients with no need for municipal care services, SCFS 2: Patients with municipal care services, including home care, and SCFS 3: Patients with residence in a short-term care facility or nursing home. The primary outcome was 90-day mortality and hospitalization. Multivariable Cox and logistic regression analyses were used to assess associations between SCFS and outcome variables. SCFS criteria were met in 35.2% of patients (668 patients, SCFS group 2 and 3). These individuals had a higher comorbidity burden and increased 90-day mortality (20.9%, p < 0.001). SCFS group 3 was independently associated with a higher risk of 90-day mortality (HR = 2.60, 95% CI: 1.27–5.29, p = 0.009), compared to group 1. ROC curve analysis showed that combining SCFS with METTS significantly improved predictive performance (DeLong’s test: p = 0.015 and p = 0.0322 in respective models). For hospitalization, SCFS group 3 was associated with hospitalization independent of age, sex, BMI, comorbidities, and readmission, when compared to SCFS group 1 (OR = 2.57, CI:1.11–6.71, p = 0.037). This association was attenuated and nonsignificant after further adjustment for METTS. SCFS is an independent predictor of 90-day mortality in older ED patients with acute dyspnea. When combined with triage scores like METTS, its predictive value improves. These findings support the potential clinical utility of incorporating frailty assessment into ED triage to aid risk stratification and guide care decisions.
Keywords: Aging; Dyspnea; ED; Frailty; Mortality